Calculation of the Coseismic Landslide Volume Using DEMs: An Example from the Yingxiu Area, Wenchuan, Sichuan, China - Xiaoli Chen; Yijian Chuan; Yankun Wei (Advances in Civil Engineering)
Volume calculation is important for quantifying the erosion driven by coseismic landslides in geomorphology. With the advent of digital elevation models (DEMs), quantifying features of landslide bodies have become possible, permitting to calculate the landslide volume in terms of elevation changes. To further test this approach, this work calculates the volume of landslides near the epicenter of the 2008 Mw 7.9 Wenchuan earthquake in the Yingxiu region, Sichuan, China, by comparing pre- and postearthquake DEMs. Results suggest that effective application of this method needs to consider the DEM resolution and eliminates background errors of individual landslides. The volume of coseismic landslides calculated by the proposed method may represent a minimum value compared to that from the existing empirical V-A formulas. Considering that it is difficult to quantify the coseismic landslide volume throughout in a broad region, this method can be applied to the preliminary stage of characterizing coseismic landslides quantitatively for some key localities of the affected area of major earthquakes.